The Influence of the Time Token Model on Biographical Text Writing Skills in Classs - Pratama, Rama Yunita; Harahap, Rosmawaty (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
Writing skills can hone student’s abilities to express opinions, feelings and channel their talents. Writing s a medium for communicating using written language. The aim of this study; first, to analyze text writing skills biography without using the time token model for class X SMAS Muhammadiyah Kisaran.  Second, to analyze text writing skills biography using the time token model for class X SMAS Muhammadiyah Kisaran. Then, to analyze the influence of the time token model on students writing skills in class X SMAS Muhammadiyah 8 Kisaran. The research method yses a two group post-test design. The population in this study was all class X SMAS students 36 control class students and 35 students experimental class. The instruments used are structure, suitability of content, linguistic rules, and accurary of spelling. Data analysis technique using analysi requirements test, homogeneity test, normality test, and test hypothesis. The research results in the control class obtained an average of 76,61 with good category, whilw in thw experimental class the average was 89,46 with very good category. Then, trough hypothesis testing, you can it is concluded that tcount >ttabel, namely 8,89>19444 so that the hypothesis (Ha) is accepted. This proves that there is a significant influence on the use of the time token model on biographical text writing skills in class X SMAS Muhammadiyah 8 Kisaran. Based on the research results, the time token model can be applied in classroom learning as an alternative solution by teachers to overcome the problems found.